Tim-1 Deficiency Aggravates High-Fat Diet-Induced Steatohepatitis in Mice - George, Jasmine; Zhang, Yuanyuan; Sloan, Jacob; Sims, Joya M.; Imig, John D.; Zhao, Xueying (Frontiers in Immunology, 2021)
Non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH) is commonly associated with obesity and characterized by excessive lipid accumulation and liver inflammation. The T cell immunoglobulin and mucin domain 1 (Tim-1), also known as hepatitis A virus cellular receptor 1 (Havcr-1) and kidney injury molecule 1 (Kim-1), has been shown to affect innate immunity-driven proinflammatory cascade in liver ischemia-reperfusion injury. However, its contribution to obesity-related NAFLD/NASH remains unknown. Thus, this study was designed to evaluate the role of Tim-1 in obesity-related liver inflammation and injury in wild-type (WT) and Tim-1-deficient (Tim-1-/-) C57BL/6J mice fed with a high-fat diet (HFD) for 5-6 months. HFD feeding induced steatosis and upregulated Tim-1 gene expression in the liver of WT mice. Surprisingly, Tim-1-/- mice on HFD diet exhibited an exacerbation of hepatic steatosis, accompanied with an elevation of protein levels of fatty acid translocase CD36 and sterol regulatory element binding protein 1 (SREBP1). Tim-1 deficiency also enhanced HFD-induced liver inflammation and injury, as evidenced by augmented increase in hepatic expression of pro-inflammatory factor lipocalin 2, infiltration of neutrophils and macrophages, and elevated serum ALT. In addition, gene expression of type I, III and IV collagens and liver fibrosis were greatly enhanced in HFD Tim-1-/- mice compared with WT mice. HFD-induced hepatic expression of YM-1, a specific mouse M2 macrophage marker, was further upregulated by deletion of Tim-1. Together, these results show that Tim-1 deficiency aggravates the effects of HFD diet on lipid accumulation and liver fibrosis, most likely through enhanced infiltration and activation of inflammatory cells.